2011
DOI: 10.1007/s00784-011-0528-9
|View full text |Cite
|
Sign up to set email alerts
|

Caries experience in a child population in a deprived area of Brazil, using ICDAS II

Abstract: The aim of the present study was to assess the caries experience of children aged 6 to 7 years old in a socially deprived suburban area of Brazil’s Federal District, using the ICDAS II system and to investigate determinants of dental caries. The survey was carried out in six public schools by three calibrated examiners, on a sample of 835 children. ICDAS II codes had to be converted into dmf/DMF components at surface and tooth levels, resulting in unfamiliar caries variables, to enable some meaningful reportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
90
2
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 28 publications
10
90
2
17
Order By: Relevance
“…The prevalence of caries found in this study is high, as all examined children presented one of more tooth surfaces with enamel caries lesion, findings that are similar to other studies that also used the same index [10,11,13].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The prevalence of caries found in this study is high, as all examined children presented one of more tooth surfaces with enamel caries lesion, findings that are similar to other studies that also used the same index [10,11,13].…”
Section: Discussionsupporting
confidence: 90%
“…The Kappa index obtained in this study was very good, indicating high level of intraexaminer agreement (0.83), similar to other studies [10,11,15]. That confirms the statement that says ICDAS has good-to-excellent reproducibility, even for raters without experience in epidemiological studies and even after a short training time [7].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Several epidemiological population-based studies have demonstrated a significant decrease in caries worldwide, a fact that is not demonstrated when the object of the study are preschool children (3). Well-designed epidemiological studies provide a picture of the population and are important tools in defining the distribution of funds for oral health programs and the implementation of preventive policies by stakeholders (4).…”
Section: Introdutionmentioning
confidence: 99%